Bacterial coinfection restrains antiviral CD8 T-cell response via LPS-induced inhibitory NK cells. Issue 1 (December 2018) - Straub, Tobias; Freudenberg, Marina; Schleicher, Ulrike; Bogdan, Christian; Gasteiger, Georg; Pircher, Hanspeter
Abstract Infection of specific pathogen-free mice with lymphocytic choriomeningitis virus (LCMV) is a widely used model to study antiviral T-cell immunity. Infections in the real world, however, are often accompanied by coinfections with unrelated pathogens. Here we show that in mice, systemic coinfection withE. coli suppresses the LCMV-specific cytotoxic T-lymphocyte (CTL) response and virus elimination in a NK cell- and TLR2/4-dependent manner. Soluble TLR4 ligand LPS also induces NK cell-mediated negative CTL regulation during LCMV infection. NK cells in LPS-treated mice suppress clonal expansion of LCMV-specific CTLs by a NKG2D- or NCR1-independent but perforin-dependent mechanism. These results suggest a TLR4-mediated immunoregulatory role of NK cells during viral-bacterial coinfections. Exposure to multiple pathogens is common in nature, yet interactions between the immune components targeting bacterial and viral pathogens during co-infection are poorly understood. Here the authors show that bacteria-derived LPS induces cytotoxic NK cells that suppress antiviral CD8 T cell response.